2018
DOI: 10.1161/atvbaha.117.310317
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin Enlarges the Vascular Lumen by Inducing the Quiescent Endothelial Cell Proliferation

Abstract: Our findings suggest a novel mechanism that may explain how quiescent ECs overcome the contact inhibition and regain the ability to proliferate for continuous vascular lumen enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Wang et al addressed this question using intermedin-null mice. 36 Intermedin, also called adrenomedulin-2, is a member of calcitonin gene-related peptide family that includes calcitonin, adrenomedullin, and amylin. 37 These peptide hormones initiate signaling via binding to calcitonin receptor-like receptors and signal propagation is controlled by three receptor activity-modifying proteins called RAMPs.…”
Section: Endothelial Control Of Vascular Lumen Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al addressed this question using intermedin-null mice. 36 Intermedin, also called adrenomedulin-2, is a member of calcitonin gene-related peptide family that includes calcitonin, adrenomedullin, and amylin. 37 These peptide hormones initiate signaling via binding to calcitonin receptor-like receptors and signal propagation is controlled by three receptor activity-modifying proteins called RAMPs.…”
Section: Endothelial Control Of Vascular Lumen Diametermentioning
confidence: 99%
“…39 Using CRISPR/Cas9 to generate intermedin (IMD)-deficient mice, together with experiments carried out in vitro , Wang et al was able to show that IMD promotes increased vascular lumen size by stimulating the proliferation of confluent endothelial cells while maintaining organized cell-cell contacts with no significant changes in overall cell shape. 36…”
Section: Endothelial Control Of Vascular Lumen Diametermentioning
confidence: 99%
“…Earlier studies have shown that ADM plays critical roles in the regulation of cardiovascular development, vasotone, endothelial barrier integrity, and tumor angiogenesis [3, 929]. Likewise, ADM2 is important for the regulation of vascular lumen enlargement, and exerts vaso- and cardio-protective effects in animals with hypertension, heart failure, ischemia reperfusion injury, obesity, or insulin resistance [3033]. By contrast, CGRPs are important for the regulation of nociception, hyperalgesia, and allodynia [3437].…”
Section: Introductionmentioning
confidence: 99%
“…AM2/IMD is widely expressed, and its actions include hypothalamic-pituitary-adrenal axis activation (6); protective effects in hypertension, heart attack, heart failure, and ischemia reperfusion injury (3,(7)(8)(9)(10)(11)(12); and promotion of adipocyte browning and reduction of insulin resistance and obesity (13,14). An AM2/IMD knockout mouse revealed a role for the peptide in vascular lumen enlargement during both normal and pathological angiogenesis by promoting endothelial cell proliferation (15). In humans, plasma AM2/IMD is elevated in heart failure (16), and a gene polymorphism is associated with hypertension, kidney dysfunction, and cerebrovascular lesions (17).…”
mentioning
confidence: 99%